Chest computer tomography is safe without additional interrogation or monitoring for modern cardiac implantable electrical devices. (8th April 2022) - Tsutsui, Kenta; Kato, Ritsushi; Mori, Hitoshi; Kawano, Daisuke; Ikeda, Yoshifumi; Matsumoto, Kei; Tanaka, Naomichi; Hoya, Hiroki; Seki, Kaname; Yokoyama, Shinji; Yoshida, Yuzuru; Iida, Shinichiro; et al.
Abstract: Introduction: Whether diagnostic computed tomography (CT) scans to cardiac implantable electronic devices (CIED) is safe in recent models remains unknown. Methods: A two‐centers observational study. Over 14 years, consecutive 2362 chest CT scans (1666 pacemakers [PMs], 145 cardiac resynchronization therapy PM, 316 implantable cardioverter‐defibrillator, and 233 cardiac resynchronization therapy defibrillator) were interrogated and monitored upon imaging. Results: Electromagnetic interference occurred only in a few old models: InSync 8040 ( n = 14), InSync III Marquis ( n = 1), and Kappa ( n = 4), which resulted no adverse events. Conclusion: CIEDs, especially recent ones, are confirmed safe on chest CT.